Accumulation of heavy metals (As, Cd, Pb, Hg) on brown algae, Padina australis, cultivated in Kima Bajo Waters, North Minahasa Regency - Hidayat, Sarif; Mantiri, Desy M.H.; Paulus, James J.H.; Lasut, Markus T.; Rumampuk, Natalie D.C.; Undap, Suzanne; Sumilat, Deiske A. (AQUATIC SCIENCE & MANAGEMENT, 2021)
Although heavy metals have relatively low levels in water column and sediments, they will not be degraded and can even be absorbed and accumulated by marine algae. Research on accumulation of heavy metals on algae was done in Kima Bajo Waters, North Minahasa Regency. The research objective was to evaluate the accumulation of four heavy metals, i.e. arsenic (As), cadmium (Cd), plumbum (Pb), and mercury (Hg), on brown macroalgae Padina australis. The alga was introduced and cultivated in the research area using bottom method. The same method was also used in the experiment. One-week acclimatization process was done prior the experiment. Sampling of algaâ€™s thallus was carried out every two weeks to measure the concentration of metals. The experiment was terminated after six weeks. Bottom sediment was also collected at the beginning of the experiment to measure the metal concentration. The results showed that the heavy metals (As, Cd, Pb, and Hg) were accumulated in the algae. The highest concentration of Cd, Pb, and Hg accumulated in the algae was 0.15 mg/kg wet weight, 3.5 mg/kg wet weight, and 0.009 mg/kg wet weight, respectively. All the concentrations were higher than the initial concentration of each metal. Accumulation of As was also occurred with the highest concentration (1,9 mg/kg wet weigh) occurred at fourth weeks; however, it was lower than the initial concentration. The accumulation varied according to type of metals and time; accumulation of Cd, Pb, and Hg were occurred on second weeks of cultivations and As on the fourth weeks. It can be concluded that cultivated alga can accumulate heavy metals.Indonesian title:Â Akumulasi logam berat (As, Cd, Pb, Hg) pada alga coklat,Â Padina australis, yang dibudidaya di Perairan Kima Bajo, Kabupaten Minahasa Utara